Diskoneksi Antara Kurikulum Bahasa Arab dan Implementasi Pembelajarannya di Madrasah Aliyah Dalam Perspektif ACTFL - Faizal Habibie; Moh. Ainin; Muassomah; Alfa Naja Imamuna; Nur Fuady Rahman (Universitas Yudharta Pasuruan, 2022)
There has been a disconnect between the Arabic language curriculum and the implementation of learning in Madrasah Aliyah which is one of the causes of the many failures of learning Arabic at the madrasa. This study aims to reveal some of the problems that occur in learning Arabic in the form of a disconnect between the Arabic curriculum and the implementation of learning at Madrasah Aliyah from the perspective of ACTFL. This study uses a qualitative method with a narrative approach that relies on the document analysis study of KMA 183, KMA 184 in 2019 and the ACTFL Proficiency Guide. The findings of this study indicate that there is a disconnect between the Arabic curriculum and the implementation of learning in Madrasah Aliyah from the aspect of material, assessment, allocation of learning time and supporting programs for learning Arabic at Madrasah Aliyah. This study suggests further studies related to overcoming the disconnection between the Arabic language curriculum and the implementation of learning and increasing Arabic learning in Madrasah Aliyah.